The problem of income inequality in the view of John Kenneth Galbraith and Milton Friedman - Zagóra-Jonszta, Urszula (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The paper presents the approach to income inequality of two great American economists: a representative of neo-institutionalism – John Kenneth Galbraith, and the creator of monetarism – Milton Friedman. Both of them dealt with this problem extensively. The paper aims at revealing differences in both seeking the sources of inequalities and ways to combat them. Although both economists were against excessive inequalities, the methods of overcoming them were perceived differently by each of them. Galbraith advocated that the state should be activated. Therefore, he proposed the implementation of various aid programs, claiming that there should not be poor people in rich countries, even if not everyone honestly uses such assistance. Moreover, various forms of poverty alleviation should be introduced in poor countries. On the other hand, Friedman concluded that the best way to mitigate income inequalities is a non-intervention approach of the state and free market should be left to work freely. According to him, only the market can reduce income disparities. He considered all programs implemented to overcome them to be unsuccessful because they cause social indolence as the number of people using these forms of help increases. In addition, the state is not a charitable institution and it should not include such a form of activity that is only appropriate for bodies specially appointed for this purpose (charity). The paper uses the source analysis method and the comparative method. The main works of both economists were examined in an attempt to highlight the specific nature of their approaches.

Artykuł przedstawia podejście do nierówności dochodowych dwóch wielkich amerykańskich ekonomistów: przedstawiciela neoinstytucjonalizmu – Johna Kennetha Galbraitha oraz twórcy monetaryzmu – Miltona Friedmana. Obaj sporo miejsca w swoich publikacjach poświęcili temu problemowi. Celem artykułu jest wykazanie różnic zarówno w poszukiwaniu źródeł nierówności, jak i sposobów ich zwalczania. Wprawdzie obaj ekonomiści byli przeciwni nadmiernym nierównościom, ale każdy z nich inaczej widział sposoby ich przezwyciężania. Galbraith uważał, że należy uaktywnić państwo. Proponował więc wdrożenie różnych programów pomocowych twierdząc, że w bogatych krajach nie powinno być ludzi biednych, nawet jeśli nie wszyscy uczciwie z takiej pomocy korzystają. Również w państwach ubogich należy wprowadzać różne formy niwelowania biedy. Natomiast Friedman uznał, że najlepszym sposobem łagodzenia różnic dochodowych jest brak interwencji ze strony państwa i pozostawienie swobody działania wolnemu rynkowi. Według niego tylko rynek potrafi zmniejszyć rozpiętości w dochodach. Wszelkie programy wdrażane w celu ich przezwyciężania uważał za nietrafione, ponieważ rozleniwiały społeczeństwo, bo rosła liczba osób korzystających z tych form pomocy. Ponadto państwo nie jest instytucją charytatywną i w jego gestii nie powinna się mieścić taka forma działania, która przystoi tylko organom specjalnie do tego powołanym (charytatywnym). W artykule zastosowano metodę analizy źródeł oraz metodę porównawczą. Wykorzystano przede wszystkim główne prace obu ekonomistów, starając się uwypuklić specyfikę ich podejścia.
Keywords: income inequality; John Kenneth Galbraith; Milton Friedman; nierówności dochodowe